Split-bolus versus triphasic multidetector-row computed tomography technique in the diagnosis of hepatic focal nodular hyperplasia: a case report - Scialpi, Michele (J Med Case Rep, 2014)
INTRODUCTION: Computed tomography and magnetic resonance imaging are able to demonstrate and to diagnose hepatic focal nodular hyperplasia when a typical pattern of a well-circumscribed lesion with a central scar is present. Our aim is to propose the split-bolus multidetector-row computed tomography technique as an alternative to the conventional triphasic technique in the detection and characterization of focal nodular hyperplasia to reduce the radiation dose to the patient. To the best of our knowledge, this is the first report regarding the application of the split-bolus computed tomography technique in the evaluation of hepatic focal nodular hyperplasia. CASE PRESENTATION: We describe a case of focal nodular hyperplasia of the liver in a 53-year-old Caucasian woman (weight 75Kg) with a colorectal adenocarcinoma histologically confirmed. An innovative split-bolus multidetector-row computed tomography technique was used that, by splitting intravenous contrast material in two boli, combined two phases (hepatic arterial phase and portal venous phase) in a single pass; a delayed (5 minutes) phase was obtained to compare the findings with that of triphasic multidetector-row computed tomography. CONCLUSIONS: Split-bolus multidetector-row computed tomography was able to show the same appearance of the lesion as the triphasic multidetector-row computed tomography technique. This is the first case demonstrating the effectiveness of the split-bolus multidetector-row computed tomography technique in the detection and characterization of focal nodular hyperplasia with a significant reduction in radiation dose to the patient with respect to triphasic multidetector-row computed tomography technique.